2013
DOI: 10.4236/ijg.2013.43056
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of MODIS LST Retrievals with <i>in Situ</i> Observations from AWS over the Lambert Glacier Basin, East Antarctica

Abstract: Satellite-derived surface temperature data is increasingly required to supplement the limited weather stations for the assessment of temperature trend over the data-sparse Antarctic Ice Sheet. To accomplish this, it is essential to assess the relationship and difference between satellite-based land-surface temperature (LST) retrieval and air temperature observation. In this study, we made a comparison between monthly averaged LST from Moderate Resolution Imaging Spectroradiometer (MODIS) and the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
(42 reference statements)
2
18
3
Order By: Relevance
“…A pilot study using Advanced Very High Resolution Radiometer data confirmed the general locations and value of very low surface temperatures ( Figure S1b; Wang & Key, 2005). We extracted minimum temperatures in the LST satellite swath data south of 70°S (gridded to a 1-km polar stereographic projection) between 15 June to 15 September for a 12-year period (2004-2016; MOD11 Collection 6 and MYD11 Collections 5 and 6; Wan, 2006;Wang et al, 2013). The 2004 winter was the earliest MODIS Collection 6 data available at the time we began our analysis.…”
Section: Methods and Datasupporting
confidence: 52%
“…A pilot study using Advanced Very High Resolution Radiometer data confirmed the general locations and value of very low surface temperatures ( Figure S1b; Wang & Key, 2005). We extracted minimum temperatures in the LST satellite swath data south of 70°S (gridded to a 1-km polar stereographic projection) between 15 June to 15 September for a 12-year period (2004-2016; MOD11 Collection 6 and MYD11 Collections 5 and 6; Wan, 2006;Wang et al, 2013). The 2004 winter was the earliest MODIS Collection 6 data available at the time we began our analysis.…”
Section: Methods and Datasupporting
confidence: 52%
“…However, since the focus of this study was on a global T air prediction, Antarctica was only marginally represented in the training data. Applications of MODIS LST to predict T air for Antarctica are limited to the study of Wang et al [19] who compared monthly averages of MODIS LST with T air in the Lambert Glacier Basin in East Antarctica.…”
Section: Introductionmentioning
confidence: 99%
“…In the first part of this paper, the Moderate-Resolution Imaging Spectroradiometer (MODIS) clear-sky land surface temperature (LST) values are evaluated against hourly series of in situ observations of snow surface temperature. Such an evaluation provides better insight than previous evaluations based on a comparison with near-surface temperature, as in Wang et al (2013). In the second section, MODIS LST values from 2000 to 2011 are compared with 3 h ERA-Interim (Dee et al, 2011) snow surface temperatures and hourly snow surface temperatures simulated by the detailed snowpack model Crocus (Brun et al, 1992;Vionnet et al, 2012).…”
mentioning
confidence: 99%